Correlation Study of Job Satisfaction and Organizational Citizenship Behavior on Employees of PT. Miduk Arta - Nikmah Indah Putri; Rahma Afwina (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to determine the relationship between job satisfaction and organizational citizenship behavior in employees of PT. Miduk Arta. The method in this study is quantitative. The sample in this study was 48 office employees. The sampling technique in this study was total sampling. Namely, all populations were used as research samples. The hypothesis in this study is that there is a positive relationship between job satisfaction and organizational citizenship behavior (OCB) in PT. Miduk Arta. Data collection using a Likert scale. In testing the proposed hypothesis, the correlation coefficient rxy = 0.685 was used. With a significance value of P <0.05, it shows that job satisfaction contributes 46.9%. So, there is a significant positive relationship between job satisfaction and organizational citizenship behavior in employees. Thus, the company can develop the organization, build a positive work environment, provide encouragement for employees to maintain job satisfaction, and increase the effectiveness and survival of the organization.